2013
DOI: 10.1056/nejmoa1212772
|View full text |Cite
|
Sign up to set email alerts
|

A No-Prophylaxis Platelet-Transfusion Strategy for Hematologic Cancers

Abstract: The results of our study support the need for the continued use of prophylaxis with platelet transfusion and show the benefit of such prophylaxis for reducing bleeding, as compared with no prophylaxis. A significant number of patients had bleeding despite prophylaxis. (Funded by the National Health Service Blood and Transplant Research and Development Committee and the Australian Red Cross Blood Service; TOPPS Controlled-Trials.com number, ISRCTN08758735.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
494
1
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(515 citation statements)
references
References 18 publications
8
494
1
12
Order By: Relevance
“…These results are consistent with improved survival in the rHuIL-12-treated groups, and with the previous reports showing that the depth and duration of severe cytopenias are correlated with adverse clinical outcomes [8,9]. We have also observed that for severe cytopenias resulting from lethal radiation exposure, a less deep (attenuated) nadir generally predicts an increased potential for survival as this effect reflects early bone marrow regeneration (Gluzman-Poltorak et al, manuscript in preparation).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with improved survival in the rHuIL-12-treated groups, and with the previous reports showing that the depth and duration of severe cytopenias are correlated with adverse clinical outcomes [8,9]. We have also observed that for severe cytopenias resulting from lethal radiation exposure, a less deep (attenuated) nadir generally predicts an increased potential for survival as this effect reflects early bone marrow regeneration (Gluzman-Poltorak et al, manuscript in preparation).…”
Section: Discussionsupporting
confidence: 91%
“…Rationale No RCTs of prophylactic platelet transfusion in septic or critically ill patients exist. Current recommendations and guidelines for platelet transfusion are based on clinical trials of prophylactic platelet transfusion in patients with therapy-induced thrombocytopenia (usually leukemia and stem cell transplant) [320][321][322][323][324][325][326][327]. Thrombocytopenia in sepsis is likely due to a different pathophysiology of impaired platelet production and increased platelet consumption.…”
mentioning
confidence: 99%
“…[5] The TOPPS was a randomized, open-label, non inferiority trial performed at 14 centers in the United Kingdom and Australia. Patients were randomly assigned to receive, or not to receive, prophylactic platelet transfusions when platelet counts were less than 10 9 10 9 /L [3,4].…”
Section: Discussionmentioning
confidence: 99%